Cross‐sectional association between oral health and retinal microcirculation. (9th March 2018) - Samietz, Stefanie; Jürgens, Clemens; Ittermann, Till; Holtfreter, Birte; Pink, Christiane; Schipf, Sabine; Biffar, Reiner; Völzke, Henry; Kocher, Thomas; Tost, Frank
Abstract: Aim: To investigate the relation between oral health status and microcirculation, we analysed the association between periodontitis and number of teeth with retinal vessel diameters in a population‐based study. Methods: We analysed data from the Study of Health in Pomerania‐TREND (SHIP‐TREND). All subjects (3, 183 for number of teeth, 3, 013 for mean probing depth and 2, 894 for mean attachment level) underwent nonmydriatic funduscopy and dental examination. We measured central retinal arteriolar (CRAE), venular (CRVE) vessel diameters and calculated arterio‐venous ratio (AVR) from static vessel analysis (SVA). Periodontal status was assessed using the case definition of the Center for Disease Control and Prevention/American Academy of Periodontology (CDC/AAP). Data were analysed by linear (CRAE, CRVE, AVR) and logistic regression (AVR < 0.8) adjusted for age, sex, smoking status, alcohol consumption, body mass index, systolic blood pressure, hsCRP and type‐2‐diabetes mellitus. Results: Only in men, significant associations were found between periodontal and retinal conditions. Severe periodontitis [β = −0.0120 (−0.0218; −0.0007 95%‐CI)] and mean probing depth [β = −0.0054 (−0.0105; −0.0002 95%‐CI)] were inversely associated with AVR; severe periodontitis [β = 3.80 (0.61; 6.98 95%‐CI)], mean probing depth [β = 1.86 (0.23; 3.49 95%‐CI)] and mean attachment level [β = 1.31 (0.34; 2.27 95%‐CI)] with CRVE and mean attachment level with CRAE [β = 0.91 (0.14; 1.69 95%‐CI)]. Conclusions: Our results point towards an association between periodontal conditions and AVR in men. Periodontitis may impact microvascular endothelium function. Improving oral health to reduce periodontitis might lead to reduced risk for other age‐related diseases.